On the In-Situ Grazing Incidence X-ray Diffraction of Electrochemically Formed Thin Films. (25th October 2017) - Reither, Sabine; Artner, Werner; Eder, Andreas; Larisegger, Silvia; Nelhiebel, Michael; Eisenmenger-Sittner, Christoph; Fafilek, Günter
Abstract : Existing designs of in-situ X-ray diffraction (XRD) cells for electrochemical experiments are usually cells in which the beam has to penetrate the electrolyte. In order to avoid strong attenuation of primary and diffracted beams, the electrolyte has to be a thin film which is a considerable restriction for electrochemical processes. In this contribution, a novel in-situ cell design is described which avoids the thin electrolyte configuration by backside-illumination of a thin metal film working electrode applied on a polyimide foil. This has the advantage that the X-rays only have to penetrate foil and sputtered electrode, resulting in high signals from the deposited material. Therefore, the cell does not need high intensity synchrotron radiation but works with a laboratory X-ray source. Problems with bulk solution resistance or inhomogeneous current-density distribution during deposition processes are also eliminated. The novel cell design was tested on the cathodic formation of Cu2 O on copper.